The Effect of Video as Media Toward Student’s Speaking Skill at SMP Islam Terpadu Bangkinang - Riri imazia; Vitri anggraini Hardi; Putri Asilestari (Culture education and technology research (Cetera), 2024)
The purpose of this research is to find out the effect of using video for teaching speaking at SMP Islam Terpadu Bangkinang. The research is conducted at SMP Islam Terpadu Bangkinang at the second semester in academic year of 2022/2023. The sample consisted of 51 students, 26 students in class VIII D and 25 students in classes VIII E. According to the research results, using video as a learning media has significant impact on learning student's outcomes as big 5% and the video very effective to supported learning process based on result ER=48,14%. Based on the findings of research, it can be concluded that the using video has significance effect on teaching speaking on descriptive text at the school.